(untitled) (Fiep Bulletin - online, 2014)
INTRODUCTION: The diagnosis of HIV/AIDS represents an event of devastating personal impact and represents a landmark in the life of the families who are subjected to this disease. Another important point is the fact that AIDS imposes new habits, such as the undergoing of rigorous treatment, the ingestion of drugs, frequent medical visits and examinations, all of which are considered very painful both for the family and for the child. OBJECTIVE: Identify feelings and expectations of HIV-positive mothers when living the experience of care for their HIV-positive children. METHODS: This is an exploratory descriptive study with qualitative approach. The sample was composed of 33 HIV-positive volunteer mothers, enrolled in the clinic of the reference public hospital for infectious illnesses, in the city of Natal/RN/Brasil. After the signature of a free and clarified assent term, data were collected by the application of a semi-structured interview, whose reports were recorded and transcripted literally. For analysis, it was used the technique of content analysis, creating categories that emerged from the proper speech. RESULTS: The prevalent categories in relation to the experience of care for an HIV-positive son were: protection, fear, donation, faith and hope. The condition of the mother as an HIV-positive herself was not evidenced as the biggest concern. Mothers prioritize the needs of the child and the care for the children and the family. CONCLUSION: These data reveal a suffering on the mothers which guides us for a better qualified attention, carried in a perspective of reinforcement of their self-esteem and self-care.